Evaluating COVID-19 Transmission Prevention Measures in Public Rental Flats (Rusunawa) - Rosyidah ‘Adilah; Prananda Navitas (Journal of Infrastructure & Facility Asset Management, 2022)
Surabaya is an urbanized area with one of the highest numbers of confirmed COVID-19 cases in Indonesia. With Surabaya's healthcare system on the brink of collapse, housing is crucial in extending healthcare facilities. Therefore, adequate housing is the most prioritized prerequisite for people to cope with the transmission rate of the virus. Unfortunately, public rental flats (rusunawa) are among the most vulnerable housing types due to their high density, lack of adequate facilities, and low environmental quality. This paper presents a two-stage investigation to uncover Coronavirus transmission prevention strategies in dense urban settlements, namely in rusunawa. First, the research observes transmission prevention strategies and measures employed by rusunawa residents and managers. Second, the investigation concludes with evaluating the effectiveness of the identified strategies and measures using cross-tabulation analysis. Data for this research was collected using questionnaires distributed among rusunawa residents and managers. Results indicate that effective prevention strategies differ across vulnerability groups. Thus, research findings can potentially help stakeholders and decision-makers enhance their approach to prevent Coronavirus transmission. Not only that, but research findings can also help inform and anticipate future outbreaks.